THE EFFECT OF RISK BASED CAPITAL, CLAIMS EXPENSE AND PREMIUM INCOME ON THE PROFIT OF CONVENTIONAL INSURANCE COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE IN 2019-2023. - Yuyun Wahyuni; Rico Nur Ilham; Muttaqien; Ristati (Journal of Accounting Research, Utility Finance and Digital Assets, 2025)
This study is to examine the effect of Risk Based Capital (RBC), Claim Expense (BK) and premium income (PP) on Profit (ROA) in conventional insurance companies listed on the Indonesia Stock Exchange (IDX) in 2019-2023. The data of this research can be accessed on the official website of www.idx.co.id. The sample in this study is 9 companies. The data analysis tool in this study uses the Data Panel Regression method with the Eviews 12 application tool. The results of the study found that Risk based capital has a negative but significant effect on profit (ROA), Claim expense has a significant positive effect on profit (ROA), Premium income has a negative not significant effect on profit (ROA).